Choline PET/CT in recurrent prostate cancer - Detti, Beatrice; Carnevale, Maria Grazia; Lucidi, Sara; Burchini, Luca; Caini, Saverio; Orsatti, Carolina; Bertini, Niccolò; Roghi, Manuele; di Cataldo, Vanessa; Fondelli, Simona; Ingrosso, Gianluca; Francolini, Giulio; et al. (Frontiers in Oncology, 2023)
Purpose Biochemical recurrence (BR) occurs in up to 40% of patients with prostate cancer (PCa) treated with primary radical prostatectomy (RP). Choline PET/CT may show, in a single-step examination, the site of tumor recurrence earlier than traditional imaging methods, particularly at low prostate-specific antigen (PSA) levels, thus influencing subsequent treatment. Methods/patients Patients with recurrent and non-metastatic prostate cancer (nmPCa), who were assessed with choline PET/CT, were included in the analysis. Based on imaging results, the following therapeutic strategies were chosen: radiotherapy to the prostatic bed, androgen deprivation therapy (ADT), and chemotherapy or stereotactic body radiotherapy (SBRT) to either the pelvic lymph nodes or distant metastases. We assessed the impact of age, PSA levels, Gleason score (GS), and adjuvant therapy on oncological outcomes. Results Data from 410 consecutive nmPCa patients with BR who underwent RP as primary treatment were analyzed. One hundred seventy-six (42.9%) patients had a negative choline PET/CT, and 234 (57.1%) patients resulted positive. In the multivariate analysis, only chemotherapy and PSA at recurrence were significant independent prognostic factors on overall survival (OS). In the PET-positive subgroup, the number of relapses, PSA post-prostatectomy, and chemotherapy impacted on OS. PSA (post-surgery and at recurrence) affected progression-free survival (PFS) in the univariate analysis. In the multivariate analysis, GS, the number of relapse sites, and PSA (post-surgery and at recurrence) were significant prognostic factors for disease-free survival (DFS). Conclusion Choline PET/CT provides better accuracy than conventional imaging for the assessment of nmPCa with BR after prostatectomy, thereby enabling salvage strategies and improving quality of life.